Three-Dimensional Tetranuclear Cd(II) Coordination Network Based on a 1,3-Alternate Calix[4]arene Derivative - Lee, Eunji; Ju, Huiyeong; Moon, Suk-Hee; Kang, Youngjin; Park, Ki-Min (Bulletin of the Korean Chemical Society, 2015)
KCI Citation Count: 3